2016
DOI: 10.1007/s12010-016-2058-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Protein Expression Profile in the Mature Nigella sativa (Black Seed)

Abstract: Nigella sativa (N. sativa) seed has been used as an important nutritional flavoring agent and in traditional medicine for treating many illnesses since ancient times. Understanding the proteomic component of the seed may lead to enhance the understanding of its structural and biological functional complexity. In this study, we have analyzed its proteome profile based on gel-based proteome mapping technique that includes one-dimensional gel electrophoresis followed by liquid chromatography and tandem mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Some methods allow the isolation of macromolecules, such as proteins. In 2016, innovative research was conducted on the proteome of Nigella sativa seeds [38]. The researchers analyzed the protein profile of NS seeds with a proteome mapping technique using one-dimensional gel electrophoresis followed by liquid chromatography and tandem mass spectrometry strategies.…”
Section: The Most Efficient Methods For Obtaining and Detecting The C...mentioning
confidence: 99%
“…Some methods allow the isolation of macromolecules, such as proteins. In 2016, innovative research was conducted on the proteome of Nigella sativa seeds [38]. The researchers analyzed the protein profile of NS seeds with a proteome mapping technique using one-dimensional gel electrophoresis followed by liquid chromatography and tandem mass spectrometry strategies.…”
Section: The Most Efficient Methods For Obtaining and Detecting The C...mentioning
confidence: 99%
“…In addition to the popular plants, some of the indigenous and underutilized plants were analyzed for their phytochemicals and physiology [ 73 ]. Proteomic profiles of plants such as Nigella sativa , Moringa oleifera , and Pseudostellaria heterophylla that are used in traditional medicine have been published [ 74 , 75 , 76 ]. Protein extraction was optimized for seagrass species Zostera muelleri and Posidonia australis , which contain hundreds of bioactive compounds and are used as cosmetic additives [ 77 , 78 ].…”
Section: Application Of Proteomics To Indigenous Plantsmentioning
confidence: 99%
“…For example, the proteins in the hydro-methanolic fraction of N. sativa seeds represented approximately 35-40% of the total dry weight and were found to separate into bands ranging from 10 to 94 kDa on SDS PAGE [14]. The majority of the identified proteins in black cumin seeds were involved in biochemical pathways involving carbohydrate metabolism, amino acid and shikimate pathway, lipid metabolism, nucleotide, cell organization and biogenesis, transport, and defense processes [15]. While detailed studies of the defined proteins were not performed, these investigators have identified a total of 277 proteins using metabolic and proteomic approaches [10].…”
Section: Introductionmentioning
confidence: 99%